Model Kurva dan Pendugaan Lama Waktu Pengeringan Tandan Kosong, Pelepah dan Serat Tandan Kosong Kelapa Sawit - Y Yuwana (Agroindustrial Technology, University of Trunojoyo Madura, 2018)
Biomassa originated from palm oil plant is potential to be processed into various industrial products. In the production line this material needs to dry into certain level of moisture content, mostly about 10% (wet basis) and commonly called as dry material. It is advantageous if the dryng time to produce a dry material can be predicted. Prediction is usually approached by setting up drying model of the material. The most common drying model in formulated in the form of moisture ratio in function of drying time in which the moisture content is calculated in dry basis. On the other, in practice, the moisture content of material is expressed in wet basis. The objectives of this research were to determine the drying curves and to predict the drying times of palm oil empty fruit bunches, stem and fiber dried from solar dying and oven drying. Three series of experiments were carried out according to the types of materials. The results of the experiments revealed as follows. The curves produced by the solar energy dryer operating at drying temperatures ranged from 42oC to 54,5oC for both empty fruit bunches and stem were quadratic whereas the curves produced by the oven having temperature of 105 oC for stem and fiber were linear and quadratic respectively. The form of curves obtained from the relationships between materials moisture contents determined in wet basis and drying times were similar to the curves of materials moisture ratios in function of drying times. The drying times of the solar energy drying for the empty fruit bunches were 20 hours dan 19.3 hours for Dura variety and Tenera variety respectively while those of stems were 16.3 hours and 17.9 hours respectively for Dura variety and Tenera variety. The drying times of the oven drying for the stems were 7.1 hours, 6.9 hours and 5.0 hours respectively for the lower, middle and upper parts of the stems. The drying times of oven drying for the fibers were 6.4 hours and 6.2 hours respectively for the outer and inner field stacks empty fruit bunches origins